2018
DOI: 10.1002/ajh.25049
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoproliferative disorders in patients with chronic myeloproliferative neoplasms: A systematic review

Abstract: Patients with a Ph-negative myeloproliferative neoplasm (MPN) may harbor or develop lymphoproliferative disorders (LPD), however, the clinical and molecular determinants of MPN and LPD co-occurrence are still uncertain. To systematically pool the available knowledge, we conducted a scoping review of literature published since January 2005 and analyzed single-patient clinical data from 50 papers reporting 214 individuals harboring both MPN and LPD. Patients had been diagnosed essential thrombocythemia (44%), po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
30
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 20 publications
6
30
1
2
Order By: Relevance
“…[1][2][3][4][5] Blood and solid cancers occur in about 17% of patients with MPN, often preceding the diagnosis of MPN: melanoma, prostate cancer and non-MPN blood cancers have been diagnosed in excess as compared with control population in North Europe registry studies. In addition to these incident events, recent studies consistently reported that MPN patients are also prone to an increased risk of developing second cancers (SC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Blood and solid cancers occur in about 17% of patients with MPN, often preceding the diagnosis of MPN: melanoma, prostate cancer and non-MPN blood cancers have been diagnosed in excess as compared with control population in North Europe registry studies. In addition to these incident events, recent studies consistently reported that MPN patients are also prone to an increased risk of developing second cancers (SC).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these incident events, recent studies consistently reported that MPN patients are also prone to an increased risk of developing second cancers (SC). [1][2][3][4][5] Blood and solid cancers occur in about 17% of patients with MPN, often preceding the diagnosis of MPN: melanoma, prostate cancer and non-MPN blood cancers have been diagnosed in excess as compared with control population in North Europe registry studies. 6 We recently published the results from a nested case-control study with 647 MPN patients with SC and 1234 matched controls (MPN patients without SC) recruited from European LeukemiaNet (ELN) centers and reported that the exposure to cytoreductive drugs, such as hydroxyurea and ruxolitinib, increases the occurrence of nonmelanoma skin cancers.…”
Section: Introductionmentioning
confidence: 99%
“…While the risk of transforming to acute leukemia has been the subject of several studies [2] less is known about the risk of developing other malignancies such as solid tumors. In this regard, the available information derives from retrospective cohort analysis [4][5][6][7][8][9][10] and registry-based population studies [11,12]. These latter may have limitations as they do not have access to information on individual treatment, mutational status, and other important clinical features.…”
mentioning
confidence: 99%
“…Among hematologic neoplasms, the risk is increased mainly for myeloid neoplasms; however, the risk for developing non‐Hodgkin lymphoma is also increased (hazard ratio 2.6) . A systematic review of published literature regarding concurrent MPN and LPN has recently been published . The authors analyzed single‐patient clinical data from 50 papers reporting 214 individuals harboring both MPN and LPN.…”
Section: Is There a Role For Cytoreductive Drugs For The Concomitant mentioning
confidence: 99%